Biodiversity decline detected in bird observations 1981–2018 around the islands of Seili, the Archipelago Sea, SW Finland - Jari Hänninen; Miro Pietilä; Katja Mäkinen; Jasmin Inkinen (Societas pro fauna et flora Fennica, 2022)
Bird sightings have been documented during the years 1981–2018 on the Seili and nearby islands in the Finnish Archipelago Sea, northern Baltic Sea. In this study, trends in sightings of bird species / groups and families or orders were classified as increasing, stable, decreasing or sporadic (random) based on monthly observation data. A total of 213 species were noticed in monitoring. Many species and groups declined during the study period, taxonomically 65 % of the bird families or orders showed decreasing abundances for over half or more than half of their species. The decline in bird diversity was evident also in the community composition of bird groups which has been narrowed down during the study period. Only a few species showed an increasing trend, most notably the White-tailed Eagle (Haliaeetus albicilla) and the Great Cormorant (Phalacrocorax carbo sinensis). Presently many bird species spend lesser time at the area than during early observation years.